Предмет: Математика,
автор: marykolessin
(-2 1/6+1/4)•(-2 2/11) помогите
Ответы
Автор ответа:
3
Ответ:
4 2/11
Пошаговое объяснение:
(-2 1/6 + 1/4) * (-2 2/11) = (-13/6 + 1/4) * (-24/11) =
((-13*2) + (1*3))/12 * (-24/11) = (-26 + 3)/12 * (-24/11) =
-23/12 * (-24/11) = 46/11 = 4 2/11
Автор ответа:
2
Ответ:
Пошаговое объяснение:
-125
Похожие вопросы
Предмет: Кыргыз тили,
автор: sindzi810
Предмет: Алгебра,
автор: Djdk
Предмет: Литература,
автор: k26729719
Предмет: Химия,
автор: madinovazhibek
Предмет: Обществознание,
автор: sanubshsh75543